Determining the Roles of Leisure Time among Adolescents and Young People and the Impact of Psychological Factors - Seyed Ali Reza Ganjeh; Hooman Namvar; Ali Reza Aghayousefi; Mehrdad Navabakhsh (Shahid Beheshti University of Medical Sciences, 2020)
Background and Objectives: The benefits of psychological activities are as significant as physical activities during leisure time. The aim of this study was to determine and recognize the roles of leisure time and the effect of psychological factors among adolescents and young people. Materials and Methods: This descriptive-analytical study was conducted via the fuzzy Delphi method to determine and identify the variables involved in the research. The statistical population included all adolescents aged 13 to 21 years in Tehran province, among whom 305 people were selected by multi-stage cluster sampling. Data collection tools  included standard questionnaires including meaning in life, generalized anxiety disorder, emotional intelligence, openness to experience, Meta-Emotion, physical health, need for Recreation, happiness, and volunteer work, and researcher-made questionnaires including recognition of personal interests, Calmness, and flourishing of talent. Data were analyzed by SmartPLS software using the structural equation method. Results: Psychological factors with mean (SD) 2.1 (0.2) improved leisure functions with mean (SD) 2.7 (0.4), P <0.01. Variables of psychological factors including anxiety with mean (SD) 1.2 (0.6), Meta-Emotion 3.1 (0.4), openness to experience 1.9 (0.4), emotional intelligence 2.6 (0.6), meaning of life 3.5 (0.8) and recognition of personal interests 0.4 (0.3) and leisure functions including relaxation with mean (SD) 1.0 (0.4), voluntary work 3.3 (0.8), health 4.5 (1.0), happiness  1.0 (0.4), talent flourishing 1.3 (0.5), and entertainment 3.4 (0.6), with indicators They have a significant relationship in the pattern, P<0.01. Also, considering the GOF=0.40, the overall fit level of the model was excellent. Conclusion: The study showed that psychological factors improved the roles of leisure time.